2019
DOI: 10.48550/arxiv.1907.03816
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Power of Comparisons for Actively Learning Linear Classifiers

Abstract: In the world of big data, large but costly to label datasets dominate many fields. Active learning, an unsupervised alternative to the standard PAC-learning model, was introduced to explore whether adaptive labeling could learn concepts with exponentially fewer labeled samples. While previous results show that active learning performs no better than its supervised alternative for important concept classes such as linear separators, we show that by adding weak distributional assumptions and allowing comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 13 publications
(16 reference statements)
1
23
0
Order By: Relevance
“…Our algorithms require the use of comparison queries, an addition which we show is necessary in many cases for active PAC and ARPU-learning. Along with recalling lower bounds from [6] which show comparisons are necessary for efficiently active learning non-homogeneous hyperplanes, we show that in the noiseless case it is impossible to ARPU-learn the uniform distribution over S 1 in a finite number of label queries. Further, even with the addition of a margin assumption we show the existence of simple distributions which require a number of label queries that is exponential in dimension.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our algorithms require the use of comparison queries, an addition which we show is necessary in many cases for active PAC and ARPU-learning. Along with recalling lower bounds from [6] which show comparisons are necessary for efficiently active learning non-homogeneous hyperplanes, we show that in the noiseless case it is impossible to ARPU-learn the uniform distribution over S 1 in a finite number of label queries. Further, even with the addition of a margin assumption we show the existence of simple distributions which require a number of label queries that is exponential in dimension.…”
Section: Introductionmentioning
confidence: 94%
“…By allowing the learner to ask more complicated questions of the oracle, such as comparing two points, Kane et al [4] showed that non-homogeneous linear separators in two-dimensions can be learned in exponentially fewer labeled samples than the PAC case. Later, Kane, Lovett, and Moran [5] extended this to higher dimensions using a complicated set of queries, and Hopkins, Kane, and Lovett [6] did the same by assuming weak concentration and anti-concentration on the distribution -conditions once again satisfied by s-concave distributions.…”
Section: Introductionmentioning
confidence: 99%
“…This encompasses not only KLMZ's [3] notion of enriched queries, but also the original "Membership query" model of Angluin [19] who allowed the learner to query any point in the overall instance space X rather than just on the subsample S ⊂ X. This model is also particularly well-studied for halfspaces where it is called the pointlocation problem [14,20,21,22,23,9], and was actually studied originally by Meyer auf der Heide [14] in the perfect learning model even before Angluin's introduction of active learning.…”
Section: Related Workmentioning
confidence: 99%
“…In this setting, the learner is given an arbitrary finite sample S ⊂ R, and must infer the labels under an adversarially chosen classifier. Variants of this model have been studied in the computational geometry [14,20,21,22,23,9], statistical learning theory [13], and clustering literatures [29,37] under various names. Formally, we say a class (X, H) is perfectly learnable with respect to a query set Q in q(n) expected queries if there exists an algorithm A such that for every n ∈ N, every sample S ⊂ X of size n, and every hypothesis h ∈ H, A correctly labels all of S with respect to h in at most q(n) queries in expectation over the internal randomness of the algorithm.…”
Section: Perfect Learningmentioning
confidence: 99%
“…Some of that work, particularly the work in online algorithms with a reject option, were targeted at non-stationary sequences of examples x. Even intervals are impossible to learn in online models, and in a supervised iid model Kivinen (1990) showed that exponentially many examples are required to learning rectangles under uniform distributions (as cited by Hopkins et al (2019); Goldwasser et al (2020)). Part of the challenge is that most definitions also require few test rejections, unlike PQ-learning's requirement of few rejections with respect to P .…”
Section: Related Workmentioning
confidence: 99%